Predicting the Geographical Distribution of Malaria-Associated Anopheles dirus in the South-East Asia and Western Pacific Regions Under Climate Change Scenarios - Liu, Xin; Song, Chao; Ren, Zhoupeng; Wang, Shaobin (Frontiers in Environmental Science, 2022)
Malaria occurrence is highly related to the geographical distribution of Anopheles dirus (An. dirus) in the South-East Asia and Western Pacific Regions (SEAR/WPR). Future climate change has been shown to alter the geographical distribution of malaria vectors. However, few studies have investigated the impact of climate change on the potential distribution of An. dirus in the SEAR/WPR. We considered future climate and land use data under two climate change scenarios for Representative Concentration Pathways (RCP4.5 and RCP8.5) and population data from five Shared Socioeconomic Pathways (SSPs), by using three machine learning models, namely Random Forest (RF), Boosted Regression Trees (BRT), and Maximum entropy (Maxent), to project the geographical distribution of An. Dirus, as well as to estimate the exposed population. A pseudo-absence dataset was generated based on the relationships between model performance and the distance from the pseudo-absence point to the occurrence point in order to improve model accuracy for projection of the Environmentally Suitable Area (ESA) and exposed human population. The results show that the pseudo-absence data corresponding to the distance of 250 km is appropriate for modeling. The RF method ultimately proved to have the highest accuracy. The predicted ESA of An. dirus would mainly be distributed across Myanmar, Thailand, the southern and eastern part of India, Viet Nam, the northern part of Cambodia, and the southern part of Laos. The future ESA is estimated to be reduced under the RCP4.5 climate change scenario. In the 2070s under RCP8.5, the reduction of ESA is even greater, especially in Thailand (loss of 35.49 ten thousand square kilometers), Myanmar (26.24), Viet Nam (17.52), and India (15), which may prevent around 282.6 million people from the risk of malaria under the SSP3 scenarios in the SEAR/WPR. Our predicted areas and potential impact groups for An. dirus under future climate change may provide new insights into regional malaria transmission mechanisms and deployment of malaria control measures based on local conditions in the SEAR/WPR’s.